Cognitive enhancement in children and adolescents: Is it in their best interests?. (21st September 2013) - Gaucher, N; Payot, A; Racine, E
Abstract Evidence suggests children and adolescents are consuming stimulants and nonstimulants in the hopes of improving academic performance through cognitive enhancement. As such, clinicians may be faced with requests to prescribe enhancers for their paediatric patients. In this article, we analyse the ethics of cognitive enhancement in paediatrics in the light of the best interests standard, a guiding principle, often used to make decisions for minors in moral, legal, social and medical contexts. Conclusion Cognitive enhancement in children and adolescents does not represent an ethical ideal that societies should strive for. Furthermore, paediatric cognitive enhancement does not meet the criteria for a minimally acceptable practice, given the health‐related risks posed by these medications and the coercive environments such a practice creates. In line with a recent policy statement by the American Academy of Neurology, ethical and clinical arguments based on the best interests of paediatric patients encourage clinicians to refrain from engaging in this practice.